2014
DOI: 10.1186/1471-2458-14-385
|View full text |Cite
|
Sign up to set email alerts
|

Community perception on biomedical research: A case study of malariometric survey in Korogwe District, Tanga Region, Tanzania

Abstract: BackgroundCommunity perception in biomedical research remains critical in Africa with many participants being driven by different motives. The objective of this study was to explore the perceived motives for women or females guardians to volunteer for their children to participate in biomedical research and to explore experiences and challenges faced by Community Owned Resource Persons (CORPs) when mobilizing community members to participate in biomedical research.MethodsThis cross sectional study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 28 publications
4
14
0
Order By: Relevance
“…The sentiments expressed above are consistent with the assertion that community engagement involves generating knowledge from research participants, sharing ideas and also empowering community members so that they become better equipped to deal with the numerous challenges they face in their lives [1]. In the current study, human capital development helped unlock the potential of the field workers and enabled them to gain knowledge and skills they required to improve their livelihoods.…”
Section: Discussionsupporting
confidence: 82%
“…The sentiments expressed above are consistent with the assertion that community engagement involves generating knowledge from research participants, sharing ideas and also empowering community members so that they become better equipped to deal with the numerous challenges they face in their lives [1]. In the current study, human capital development helped unlock the potential of the field workers and enabled them to gain knowledge and skills they required to improve their livelihoods.…”
Section: Discussionsupporting
confidence: 82%
“…Social scienti c research into local participation in biomedical research projects in Africa has similarly showed a wide range of motivational factors. A research study conducted in Tanzania on the reasons given by mothers and guardians to explain their decision to enrol their children in malariometric trials, for example, demonstrated to the importance of gaining access to better healthcare services [58]. A similar survey conducted in Malawi found that a variety of direct nancial or material bene ts (soap, groundnut paste, orange juice, transportation money, tablecloths, mosquito nets, water basins, and iron tablets) was important in accounting for a high level of community participation [45,59].…”
Section: Discussionmentioning
confidence: 99%
“…Active community participation through these platforms in prioritizing malaria related messages to be developed and activities to be deployed was then found rewarding, created a conducive environment for ownership and utilization of knowledge produced at individual and village levels in relation to health [40, 4244]. …”
Section: Discussionmentioning
confidence: 99%